2015
DOI: 10.1037/xhp0000051
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic arousal and attentional orienting to visual threat are predicted by awareness.

Abstract: The rapid detection and evaluation of threat is of fundamental importance for survival. Theories suggest that this evolutionary pressure has driven functional adaptations in a specialized visual pathway that evaluates threat independently of conscious awareness. This is supported by evidence that threat-relevant stimuli rendered invisible by backward masking can induce physiological fear responses and modulate spatial attention. The validity of these findings has since been questioned by research using stringe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
30
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 91 publications
9
30
2
Order By: Relevance
“…That is, our results fail to provide evidence that, during CFS, traditional pacmen stimuli can induce figure-ground processes that might lead to a differential effect for stimuli able to induce a surface percept. This observation is consistent with a broader set of recent studies focusing on the extent to which mid-and high-level stimuli are represented during CFS (Faivre & Koch, 2014;Gayet, Van Der Stigchel, & Paffen, 2014;Hedger, Adams, & Garner, 2015;Hesselmann & Knops, 2014;Hesselmann & Moors, 2015;Heyman & Moors, 2014;Moors, Huygelier, Wagemans, de-Wit, & van Ee, 2015). That is, there is converging evidence that suppressed stimuli are processed to a limited extent during CFS and that any process that requires complex integration of several features of the suppressed stimulus is unlikely to take place.…”
Section: Discussionsupporting
confidence: 75%
“…That is, our results fail to provide evidence that, during CFS, traditional pacmen stimuli can induce figure-ground processes that might lead to a differential effect for stimuli able to induce a surface percept. This observation is consistent with a broader set of recent studies focusing on the extent to which mid-and high-level stimuli are represented during CFS (Faivre & Koch, 2014;Gayet, Van Der Stigchel, & Paffen, 2014;Hedger, Adams, & Garner, 2015;Hesselmann & Knops, 2014;Hesselmann & Moors, 2015;Heyman & Moors, 2014;Moors, Huygelier, Wagemans, de-Wit, & van Ee, 2015). That is, there is converging evidence that suppressed stimuli are processed to a limited extent during CFS and that any process that requires complex integration of several features of the suppressed stimulus is unlikely to take place.…”
Section: Discussionsupporting
confidence: 75%
“…Although the current study does not provide direct evidence on the possible mechanisms underlying the observed effects, it is postulated that a specialized subcortical visual pathway (through the superior colliculus and the pulvinar to the amygdala) is dedicated to detecting threat-related signals outside of conscious awareness (Hedger et al, 2015). This idea has been supported by converging evidence showing that subliminal threat-related visual stimuli elicit enhanced neural and physiological responses in comparison with non-threat stimuli.…”
Section: Discussionmentioning
confidence: 80%
“…For example, Hedger, Adams and Garner (2015a) recently showed that the advantage of fearful faces breaking suppression faster than neutral ones is predicted by effective contrast of the stimuli. Furthermore, another recent study by the same group observed that attentional orienting due to threat stimuli is completely absent when threatening stimuli were rendered completely invisible ( Hedger, Adams & Garner, 2015b ). Other studies have cast doubt on whether invisible words can be processed ( Heyman & Moors, 2014 ), numerosity can be extracted during suppression ( Liu et al, 2013 ; Hesselmann et al, 2014 ; Hesselmann & Knops, 2014 ), or integration between a suppressed visual looming stimulus and a supraliminal auditory stimulus can occur ( Moors et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%